Doing Business 2007 : How to Reform - World Bank (Doing Business, 2006)
Doing Business 2007 focuses on reforms, identifies top reformers in business regulation, and best practices in how to reform. This volume is the fourth in a series of annual reports investigating global regulations that enhance business activity and those that constrain it. Co-sponsored by the World Bank and the International Finance Corporation - the private sector arm of the World Bank Group - this year's report measures quantitative indicators on business regulations and their enforcement compared across 175 countries - from Afghanistan to Zimbabwe - and over time. Doing Business 2007 updates indicators developed in the three preceding reports. The ten indicators are: starting a business, dealing with licenses, hiring and firing, registering property, getting credit, protecting investors, trading across borders, paying taxes, enforcing contracts, and closing a business. The indicators are used to analyze economic and social outcomes, such as informality, corruption, unemployment, and poverty. This annually published report gives policymakers the ability to measure regulatory performance in comparison to other countries, learn from best practices globally, and prioritize reforms. This year's report covers 20 additional countries